(3JgPjH GddZIs - (3eMeO Hf CMeO Hf GdCRgQj GdgQhj, CHh efUhQ,J (B370 (3g` s
(3ChdgG (B:s
(3bGd GHh efUhQ eMeO Hf CMeO Hf WdMI Hf fhM Hf GdGRgQ GdGRgQi GdMeO ddg Pi GdMhd hGdbOQI hcJGHi gPG hEf de jcf LGeYkG deYGfi GdJfRjd HGH PcQ GdGFeI GdPjf EYJeGOi Ydjge ajeG LeYJ ai gPG GdcJGH s
(3BNQgG (B:s
(3jfJgi CKfGA cJGH GdKdGKi GdUMjM ef MQa GdZjf HGH GdZjf hGdbGa s
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B230s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B515s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GddZIs